PENGUJIAN KUALITAS KELAYAKAN SISTEM INFORMASI KEUANGAN SEKOLAH SMK YPT2 PURBALINGGA MENGGUNAKAN MODEL RAPID APPLICATION DEVELOPMENT - Muh Sofi'i Sofi'i; Wika Purbasari; Novita Setianti (LPPM STMIK Widya Utama, 2019)
Building a quality software is not easy. Many things must be considered in making a quality software. The more quality a software or application will be, the more expensive the price will be sold. YPT 2 Vocational School currently has an Integrated Financial Information System, but it is still running on a webbased platform. Foundations and school management have agreed to increase the reach of the system by utilizing the Android platform. In connection with the foregoing, a feasibility test for the School Financial Information System that is currently operational. Based on the literature review, it was found that the validation of the test could use the Rapid Application Development (RAD) model. The RAD testing involved competent parties in the system, including foundations, management, teachers and students. Testing was carried out by 20 respondents, and based on test results obtained information that value obtained from testing for completeness of the features obtained by the smallest standard error value of 0.008 and the highest error of 0.058. The ease of use variable with the smallest standard error is 0.013 and the highest is 0.063. The last variable tested was flexibility with the smallest error value of 0.015 and the highest 0.035. Based on research that has been done, it can be concluded that the YPT Financial Information System is declared suitable for use by users. The results of this study recommend that in creating a new platform, the Android platform, later to continue to base on the DBMS model that is currently tested. Developers can create a fire rest by utilizing a model of the system that is already running, so that the addition of service coverage will not at all interact with the controller and the model related to the presentation of information.